2020
DOI: 10.2478/mape-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Wear Resistance Improvement of Equipment for Production of Building Ceramics by Hardfacing with Flux-Coerd Electrodes based on Fe-Ti-B-C System

Abstract: In this work were analyzed factors that leads to wearing of equipment of production engineering, construction, oil and gas, woodworking, tillage industries. Was established that traditional hardfacing materials based on the Fe-Cr-C system are not effective for improvement of abrasion resistance of elements of equipment for production of ceramic building materials due to working conditions. The aim of this work was to increase a durability of that equipment by using of flux cored electrodes with reaction compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The experience gained from operating laboratory, pilotscale, and industrial auger presses of various designs, along with data from literature sources [14], has allowed the generalisation of their restoration practices. The presence of abrasive materials, such as mill scale, aspirational dust from steelmaking processes, metallurgical slags, and fine fraction scrap, causes wear on the leading surface of the screw blades, as shown in Fig.…”
Section: A Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…The experience gained from operating laboratory, pilotscale, and industrial auger presses of various designs, along with data from literature sources [14], has allowed the generalisation of their restoration practices. The presence of abrasive materials, such as mill scale, aspirational dust from steelmaking processes, metallurgical slags, and fine fraction scrap, causes wear on the leading surface of the screw blades, as shown in Fig.…”
Section: A Generalmentioning
confidence: 99%
“…One important approach for restoring machine parts is the formation of a wear-resistant surface using flux-cored arc welding (FCAW) [12] and wire arc additive methods [13]. Prysyazhnyuk [14] demonstrated the application of an Fe-Ti-Mo-B-C system for repairing auger presses in the ceramic industry. Industrial testing of the clay confirmed the laboratory research results.…”
Section: Introductionmentioning
confidence: 99%
“…Fe-B-С system flux-cored wire electrode hardfacing technology is used in different industry branches for equipment worn parts reinforcement [32][33][34][35][36]. However, are becoming more widespread by Fe-Cr-B-C and Fe-Ti-Cr-B-C system alloys, which have the best mechanical properties and wear resistance [8, [37][38][39][40][41]. Moreover, these borides are based on the triple alloying system Fe-C-B, allowing to reduce quantity of more expensive, but more wide-spread alloying elements, comprising strengthening phase, such as Cr, Mo, V.…”
Section: Researchmentioning
confidence: 99%